Ecological Networks and Community Attachment and Support Among Recently Resettled Refugees. Issue 3 (25th March 2018) - Soller, Brian; Goodkind, Jessica R.; Greene, R. Neil; Browning, Christopher R.; Shantzek, Cece
Abstract: Interventions aimed at enhancing mental health are increasingly centered around promoting community attachment and support. However, few have examined and tested the specific ecological factors that give rise to these key community processes. Drawing from insights from the ecological network perspective, we tested whether spatial and social overlap in routine activity settings (e.g., work, school, childcare) with fellow ethnic community members is associated with individuals' attachment to their ethnic communities and access to social resources embedded in their communities. Data on routine activity locations drawn from the Refugee Well‐Being Project (based in a city in the Southwestern United States) were used to reconstruct the ecological networks of recently resettled refugee communities, which were two‐mode networks that comprise individuals and their routine activity locations. Results indicated that respondents' community attachment and support increased with their ecological network extensity—which taps the extent to which respondents share routine activity locations with other community members. Our study highlights a key ecological process that potentially enhances individuals' ethnic community attachment that extends beyond residential neighborhoods. Highlights: Advances the ecological network approach, which focuses on spatial patterns of routine activities. Examines how ecological processes contribute to sense of community attachment and support. Identifies avenues for enhancing community attachment and social capital among resettling refugees. Reveals impact of activity locations beyond residential neighborhood on shaping community sentiment.